NEW MEDIA AND RECRUITMENT - Anita Maharani (Innovative Issues and Approaches in Social Sciences, 2018)
The purpose of this article is to give an overview of how recruitment process as in part of human resource management shifts, from traditionally paper use to digital. This article delivers knowledge on how new media plays important role in the organization, especially in terms of human resource management. Recruitment is one of human resource management activity, and along with that, it will be followed by a selection. However, by using new media and in this case, is through social media networks, a corporation or an organization will safes time and reach more potential talented.